Analisis Intensitas Hujan dan Estimasi Debit Puncak Menggunakan Metode Mononobe Sherman dan Rasional di Kabupaten Kediri - Muhammad Vicxi Pakurohtul Rohman; Eko Siswanto (Jurnal Konstruksi, 2026)
Kediri Regency is a region in East Java Province that has a tropical monsoon climate with two distinct seasons, namely the rainy season and the dry season. High rainfall fluctuations in 2023, with an annual total of 1,330 mm and a peak of 391 mm in February, have the potential to cause local flooding. This study aims to analyze monthly rainfall patterns and calculate short-term rainfall intensity (1, 2, 6, and 24 hours) using the Mononobe and Sherman empirical methods, then evaluate flood potential using the Rational method. The results show that the highest rainfall intensity occurred in February with a value of 4.842 mm/hour (duration of 1 hour), while the estimated peak discharge reached 0.121 m³/s for an area of 10 ha with a runoff coefficient of 0.9. These conditions indicate that even though the rainfall intensity is not considered extreme, rainfall accumulation and low drainage capacity can cause flooding in the urban area of Kediri. These findings are an important basis for drainage system planning, flood mitigation, and the preparation of a local Intensity-Duration-Frequency (IDF) curve as a reference for regional hydrological design.